Eksperimen Mini Erupsi Gunung Berapi Berbasis Media Sederhana Upaya Peningkatan Keterampilan Proses Sains - Ria Suherman; Adjeng Dwi Kartika; Nurul Hasanah (Jurnal Budi Pekerti Agama Islam, 2025)
This practicum aims to understand the process of volcanic eruptions through a simple chemical reaction simulation between baking soda and vinegar. This reaction produces carbon dioxide gas that pushes the mixture out of the bottle, resembling magma eruption from a volcanic crater. The activity was carried out using simple materials such as used plastic bottles, aluminum foil, and common household items. The procedure involved shaping a volcano using aluminum foil around the bottle, then adding baking soda, dish soap, food coloring, and vinegar as the reaction trigger. Observations showed that after the vinegar was poured into the bottle, a foamy red/orange eruption occurred, mimicking lava spewing from a volcanic crater. This simulation demonstrates that the combination of an acid (vinegar) and a base (baking soda) produces carbon dioxide gas, which forces the mixture outward in a dramatic manner. This practicum not only helps students concretely understand scientific concepts but also enhances their observation, critical thinking, and scientific communication skills through simple experimental activities.